The Effect of Work Environment and Occupational Health and Safety on Employee Performance by Mediation of Job Satisfaction in Technical Service Officers PT PLN (Persero) UP3 Samarinda - Hendra Irawan; Asyhari Asyhari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the influence of the work environment and occupational health and safety (OHS) on employee performance, with job satisfaction acting as a mediating variable among technical service personnel at PT PLN (Persero) UP3 Samarinda. The research background stems from the critical importance of creating a conducive work environment and implementing an optimal OHS system to improve human resource performance in the electricity sector, which is classified as a high-risk industry. A well-structured work environment fosters comfort and motivation among employees, while effective OHS implementation reduces the likelihood of workplace accidents and enhances the sense of security, ultimately driving productivity. The research adopts a quantitative approach with a causal design. Data were collected through a Likert-scale questionnaire administered to 237 respondents and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to examine the relationships between variables comprehensively. The results demonstrate that both the work environment and OHS have a significant and positive effect on job satisfaction. Furthermore, job satisfaction significantly influences employee performance and serves as a mediating factor in the relationship between the work environment, OHS, and performance outcomes. These findings indicate that employees who perceive a safe and supportive work environment tend to show higher satisfaction levels, which translates into better performance. The study concludes that enhancing work environment quality and implementing effective safety programs have both direct and indirect positive impacts on employee performance through job satisfaction. Managerial implications include upgrading workplace facilities and infrastructure, optimizing safety training programs, and strengthening job satisfaction through structured reward systems and clear career development plans. This aligns with modern human resource management practices that emphasize employee well-being as a foundation for sustainable productivity.